The role of unemployment and job change when estimating the returns to migration - Julian Emmler; Bernd Fitzenberger (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Estimating the returns to migration from East to West Germany, this paper focuses on pre-migration employment dynamics, earnings uncertainty, and job change in the source region. Migrants are found to be negatively selected with respect to labor market outcomes, with a large drop in earnings and employment during the last few months before migration. We find sizeable positive earnings and employment gains of migration both in comparison to staying or job change. The size of the gains varies considerably with pre-migration earnings and with the counterfactual considered. Future migrants have worse expectations for their labor market prospects in the East and migrants show a greater openness to mobility.
Keywords: J61; R23; O15; P25; 330; migration; returns; selection; unemployment; moving costs